Increased maternal phenylalanine concentration may influence not only fetal heart structural development but also cardiovascular function and pulmonary tissue development in humans – a case report - Sylwestrzak, Oskar; Murlewska, Julia; Sokołowski, Łukasz; Tadros-Zins, Monika; Krekora, Michał; Maroszyńska, Iwona; Respondek-Liberska, Maria (Prenatal Cardiology, 2023)
A case of the fetus exposed to elevated phenylalanine concentration, who presented structural and functional cardiovascular changes and pulmonary injury in uncontrolled phenylketonuria of the pregnant woman. Continued fetal echocardiographic monitoring in the third trimester of pregnancy allowed to present fetal functional cardiovascular abnormalities and suspect neonatal persistent pulmonary hypertension. To the best of our knowledge, prenatal detection of persistent pulmonary hypertension in the case of maternal phenylketonuria on the newborn has not been reported before, and increased phenylalanine might be an additional factor influencing pulmonary tissue development.